Construction and Validation of Indian Consumer Ethnocentrism Scale: The Ice-Scale - Riddhish N. Joshi; Dr. Yogesh C. Joshi (Gadjah Mada International Journal of Business, 2021)
Globalization has unlocked and exposed domestic and overseas marketers to superior market opportunities. Additionally, it presents consumers worldwide with a vast number of local and foreign brand choices. Indian consumers, also now, have a broader choice of merchandise at their disposal as economic liberalization and privatization along with globalization have reduced the barriers to trade. In such a setting, the concept of consumer ethnocentrism can deliver deep insights about the preference of consumers toward domestic merchandise. The study aims to develop the Indian Consumer Ethnocentrism Scale (ICE-Scale) and validate the same. Data are collected using a structured questionnaire from urban and rural regions. The study constructed the Indian Consumer Ethnocentrism Scale (ICE-Scale), explored its dimensionality on a sample of 450 respondents, and validated the scale with another sample of 450 using exploratory factor analysis. It was established that the ICE-Scale encompasses two dimensions, namely, protective ethnocentrism and patriotic ethnocentrism. Additionally, the validity testing for the proposed scale and both the constructs were conducted through confirmatory factor analysis. The study advances the existing pool of information in the field of international economics, consumer psychology and global marketing. It also assists domestic producers to get an improved understanding of consumers’ ethnocentric tendencies which in turn would assist them in choosing superior marketing strategies and boosting their sales. The study will not only deliver certain social and policymaking insights to the domestic firms and government but also to the foreign firms functioning or planning to operate in India.